The contribution of the design characteristics of public spaces in enhancing social interactionsin social housing: The case of social neighborhood of 520, M’sila, Algeria - Faid, Bachir; Layeb, Hafid (Technium Social Sciences Journal, 2022)
Thispaper studiesthe public outdoor spaces in social housing and the role ofdesign characteristics of the public spaces and their impacts on enhancing social interactions. However, since 1962, one may notice that Algeria has opted for social housing in its housing programmes to meet the growing demand; but social housing did not satisfy the residents’ needs as authorities focused on the quantity of residential neighborhoods,but they neglected designs of public spaces, which urged us to study them to see the extent to which the design characteristics of these spaces contribute to theachievement of social interactions between inhabitants.The research relies on the analytical approach by observing and analyzing the design characteristics of public spaces in social housing and their role in promoting social interactions in the neighborhood of 520 in M’sila, Algeria. A questionnaire form is addressed to the neighborhood residents to evaluate social interactions. The results of the study show dissatisfaction of the residents and the need to take into account the design characteristics during planning because of their importance in promoting social interactions